KONSEP ESTETIKA BAUMGARTEN DAN ESTETIKA HINDU - Amelia Purwandini; Kadek Rudi Sanjaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Aesthetics if viewed in a general sense has similarities with aesthetics in Hindu's view which is essentially a view of the sense of Beauty (Lango) of an object being observed. However, Hindu aesthetics are tied by Hindu values that are based on the teachings of the Vedic scriptures. There are some concepts that become fundamental foundations and are considered important in Hindu aesthetics such as; The concept of chastity, the concept of truth, and the concept of balance. The concept of chastity (Siwan) essentially concerns divine values that also include the Yadnya and Taksu. Hindus, as seen in Bali, has a aesthetic view tied by the spiritual values of the Godhead in accordance with the teachings of Hinduism. The Hindu leaders claimed that God was the most beautiful and the source of all beauty. In India, God in his form Shiva Nataraja with his dance is said to be the creator of music and dance as well as the creator of the Supreme art. For this belief, Hindu people believe that everything that is artistic value is God's creation.The problem in this case is the aesthetic concept in a work of art and the meaning contained in a created artwork. The theory used is aesthetic theory with the observation method using the five senses. The results of observations are known to consist of themes of philosophy, rules, and ethics in a work of art. The mandate is that one must be able to express a taste into a work that has high aesthetic value in it. The aesthetics of Balinese artwork, especially paintings, ornaments or Balinese art, is formed from several elements and instruments that asking complement, as well as fulfilling the Hindu aesthetic of Satyam, Siwam, and Sundaram. The meaning contained in a Balinese art work include: The Meaning of Hindu theology consists of God's source of everything, the God can be realized with the symbol by being poured into the form of painting in accordance with the concept of Tri Purusa namely Sadasiwa; Susila's meaning consists of social strata and literary sociology; And the meaning of the event consists of the meaning of self-purification, religious ceremony facilities and used as interior to enjoy its beauty.